Snazarus and its human ortholog SNX25 modulate autophagic flux. - Lauzier, A.; Bossanyi, M.F.; Larcher, R.; Nassari, S.; Ugrankar, R.; Henne, W.M.; Jean, S. (Journal of Cell Science, 2022)
Macroautophagy, the degradation and recycling of cytosolic components in the lysosome, is an important cellular mechanism. It is a membrane-mediated process that is linked to vesicular trafficking events. The sorting nexin (SNX) protein family controls the sorting of a large array of cargoes, and various SNXs impact autophagy. To improve our understanding of their functions in vivo, we screened all Drosophila SNXs using inducible RNA interference in the fat body. Significantly, depletion of Snazarus (Snz) led to decreased autophagic flux. Interestingly, we observed altered distribution of Vamp7-positive vesicles with Snz depletion, and the roles of Snz were conserved in human cells. SNX25, the closest human ortholog to Snz, regulates both VAMP8 endocytosis and lipid metabolism. Through knockout-rescue experiments, we demonstrate that these activities are dependent on specific SNX25 domains and that the autophagic defects seen upon SNX25 loss can be rescued by ethanolamine addition. We also demonstrate the presence of differentially spliced forms of SNX14 and SNX25 in cancer cells. This work identifies a conserved role for Snz/SNX25 as a regulator of autophagic flux and reveals differential isoform expression between paralogs.